Análise do ensino e da aprendizagem de crianças com surdez incluídas no ensino regular - Barbosa, Regiane da Silva (2009)
The inclusion provided access for people with special educational needs to regular education. Follow and analyze how it has been the inclusion of these children in regular schools is one way to contribute to the success of inclusion and education. This idea was developed in this research, focusing on deafness. This is a qualitative research, whose objective is to investigate and analyze how it is getting teaching and learning of deaf children included in regular schools from a midsize city in São Paulo. Participated in this research three deaf children and their teachers, resulting in three dyads. The instruments for information collection were questionnaires done with parents of participating children and their teachers, and classroom observation and recording of observations and information in a diary. The information analysis indicates that the main difficulties of teaching are in communication with the child with deafness and teaching without grounding on speech; The main difficulty in learning is to understand the speech in the classroom and in interpreting questions. The research results show lack of knowledge, training, information and support to work with these children, in other words, to the success of inclusion and quality education.